Bioluminescence Imaging Study of Spatial and Temporal Persistence of Lactobacillus plantarum and Lactococcus lactis in Living Mice - Daniel, Catherine (American Society for Microbiology, 2013)
Lactic acid bacteria, especially lactobacilli, are common inhabitants of the gastrointestinal tract of mammals, for which they have received considerable attention due to their putative health-promoting properties. In this study, we describe the development and application of luciferase-expressing Lactobacillus plantarum and Lactococcus lactis strains for noninvasive in vivo monitoring in the digestive tract of mice. We report for the first time the functional in vitro expression in Lactobacillus plantarum NCIMB8826 and in Lactococcus lactis MG1363 of the click beetle luciferase (CBluc), as well as Gaussia and bacterial luciferases, using a combination of vectors, promoters, and codon-optimized genes. We demonstrate that a CBluc construction is the best-performing luciferase system for the noninvasive in vivo detection of lactic acid bacteria after oral administration. The persistence and viability of both strains was studied by bioluminescence imaging in anesthetized mice and in mouse feces. In vivo bioluminescence imaging confirmed that after a single or multiple oral administrations, L. lactis has shorter survival times in the mouse gastrointestinal tract than L. plantarum, and it also revealed the precise gut compartments where both strains persisted. The application of luciferase-labeled bacteria has significant potential to allow the in vivo and ex vivo study of the interactions of lactic acid bacteria with their mammalian host.